Using Project-Based Learning to Enhance STEM Education in Elementary Science Classrooms - Bilski, Kaela C (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
As the demand for highly qualified workers continues to rise in STEM career fields, US schools are responding by placing a greater emphasis on STEM education with the goal of improving both student achievement and interest in STEM fields. Despite the trend toward increased STEM initiatives in schools, there has been limited research into best teaching practices for STEM education and many teachers express discomfort with both STEM content and pedagogy. One approach to STEM education that research has shown to be highly effective is Project-Based Learning (PBL). This article explores the impact of PBL as well as outlines a pedagogical framework for implementing PBL in the science classroom to support student achievement and increase attitudes in STEM content areas.